Weed management strategies effect on glyphosate‐tolerant maize and soybean yields and quality. Issue 1 (28th August 2020) - Smedbol, Élise; Lucotte, Marc; Tremblay, Gilles; Moingt, Matthieu; Paquet, Serge; Bernier Brillon, Jérôme; Samson‐Brais, Émile
Abstract: Weed management (WM) is necessary to prevent crop losses through competition with weeds and maintain high yields. However, in the case of glyphosate‐tolerant (GT) crops, phytotoxic effects can occur after glyphosate‐based herbicide (GBH) applications, which could impact yields and quality. In order to assess the agronomic performance of six WM strategies on GT soybean [ Glycine max (L.) Merr.] and maize ( Zea mays L.), field experiments were conducted in randomized blocks replicated four times (T1 : Mechanical weeding; T2 : Other herbicide application [Soybean: Chlorimuron ethyl + Imazethapyr] [Corn: Saflufenacil + Dimethenamid‐P]; T3 : One GBH application; T4 : One GBH + other herbicide application [Soybean: Imazethapyr] [Corn: S‐metolachlor + Mesotrione]; T5 : Two GBH applications; T6 : Two GBH applications + other herbicide application [Soybean: Chlorimuron ethyl + Imazethapyr] [Corn: S‐metolachlor + Mesotrione]). In soybean, T1 was the least productive treatment with an average yield of 2, 652 kg ha −1, while T4, T5, and T6 produced significantly higher yields (4, 315, 4, 646, and 4, 248 kg ha −1 respectively). However, the protein content was higher in T1 (42%) than in T3‐6 (40.85, 40.55, 40.68, and 40.65%), as well as the linolenic acid content whereas the total oil content was significantly lower. For maize, there were no significant differences in yields nor in nutritional content for all treatments. These findings question the systemic usage of GBHs in GT crops. If unnecessary, GBH applications could be reduced, which would relieve the selection pressure for glyphosate‐resistant weeds, especially in the case of GT soybean and maize crop rotation.